Materials, Designs and Standards Used in Ski-Boots for Alpine Skiing - Matteo Moncalero; Marco Nicotra; Martino Colonna (MDPI AG, 2013)
This review article reports the recent advances in the study, design and production of ski-boots for alpine skiing. An overview of the different designs and the materials used in ski-boot construction is provided giving particular emphasis to the effect of these parameters on the final performances and on the prevention of injuries. The use of specific materials for ski-boots dedicated to different disciplines (race skiing, mogul skiing, ski-mountaineering etc.) has been correlated with the chemical and physical properties of the polymeric materials employed. A review of the scientific literature and the most interesting patents is also presented, correlating the results reported with the performances and industrial production of ski-boots. Suggestions for new studies and the use of advanced materials are also provided. A final section dedicated to the standards involved in ski-boot design completes this review article.